SiiA and SiiB are novel type I secretion system subunits controlling SPI4-mediated adhesion of Salmonella enterica - Wille, Thorsten; Wagner, Carolin; Mittelstädt, Wilrun; Blank, Kathrin; Sommer, Erik; Malengo, Gabriele; Döhler, Daniela; Lange, Anna; Sourjik, Victor; Hensel, Michael; Gerlach, Roman G. (Cellular microbiology, 2014)
The giant non-fimbrial adhesin SiiE is essential to establish intimate contact between Salmonella enterica and the apical surface of polarized epithelial cells. SiiE is secreted by a type I secretion system (T1SS) encoded by Salmonella Pathogenicity Island 4 (SPI4). We identified SiiA and SiiB as two regulatory proteins encoded by SPI4. Mutant strains in siiA or siiB still secrete SiiE, but are highly reduced in adhesion to, and invasion of polarized cells. SiiA and SiiB are inner membrane proteins with one and three transmembrane (TM) helices respectively. TM2 and TM3 of SiiB are similar to members of the ExbB/TolQ family, while the TM of SiiA is similar to MotB and a conserved aspartate residue in this TM is essential for SPI4-encoded T1SS function. Co-immunoprecipitation, bacterial two-hybrid and FRET demonstrate homo- and heterotypic protein interactions for SiiA and SiiB. SiiB, but not SiiA also interacts with the SPI4-T1SS ATPase SiiF. The integrity of the Walker A box in SiiF was required for SiiB-SiiF interactionand SiiF dimer formation. Based on these data, we describe SiiA and SiiB as new, exclusively virulence-associated members of the Mot/Exb/Tol family of membrane proteins. Both proteins are involved in a novel mechanism of controlling SPI4-T1SS-dependent adhesion, most likely by formation of a proton-conducting channel.
First published online 5 November 2013
Gesehen am 22.10.2020